2002
DOI: 10.1016/s0006-3495(02)75209-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the First Steps of the Reaction Catalyzed by HIV-1 Protease

Abstract: The mechanism of the first steps of the reaction catalyzed by HIV-1 protease was studied through molecular dynamics simulations. The potential energy surface in the active site was generated using the approximate valence bond method. The approximate valence bond (AVB) method was parameterized based on density functional calculations. The surrounding protein and explicit water environment was modeled with conventional, classical force field. The calculations were performed based on HIV-1 protease complexed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…The cleavage site has been studied at the DFT-BLYP level of theory with a PW basis set. The two reaction coordinates that were constrained in order to simulate the hydrolysis reaction were (i) the C (SUB) -O (WAT) distance, which has already been suggested in previous studies, 6,7,15 and (ii) the N (INT) -H (Asp25) distance, which has been identified in this work by performing an unbiased scan of the free-energy surface with the CAFES method. 42 The reaction is characterized by two distinct energy barriers, one for the nucleophilic attack of the water molecule (TS1) and the second for the protonation of the peptide bond nitrogen (TS2) that leads A comparison of our QM/MM results with previous studies and with the analogous QM/MM simulations in which the protein electric field is switched off indicates that, at least for the first reaction step, the electrostatic field generated by the residues surrounding the cleavage site plays a fundamental role in stabilizing the Asp dyad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cleavage site has been studied at the DFT-BLYP level of theory with a PW basis set. The two reaction coordinates that were constrained in order to simulate the hydrolysis reaction were (i) the C (SUB) -O (WAT) distance, which has already been suggested in previous studies, 6,7,15 and (ii) the N (INT) -H (Asp25) distance, which has been identified in this work by performing an unbiased scan of the free-energy surface with the CAFES method. 42 The reaction is characterized by two distinct energy barriers, one for the nucleophilic attack of the water molecule (TS1) and the second for the protonation of the peptide bond nitrogen (TS2) that leads A comparison of our QM/MM results with previous studies and with the analogous QM/MM simulations in which the protein electric field is switched off indicates that, at least for the first reaction step, the electrostatic field generated by the residues surrounding the cleavage site plays a fundamental role in stabilizing the Asp dyad.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established that CO ) d(C-(SUB) -O (WAT) ) is an appropriate reaction coordinate for describing this part of the reaction. 6,7,15 For chemical step 2, several reaction coordinates are possible. For this reason, 3.0 ps of QM/MM-CAFES 42 simulation were performed to obtain qualitative information about the possible reaction coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…16 The relatively simple structure of the active site is nevertheless the origin of some problems, which are still the source of many scientific debates. Generally, experimental 17, 18, 19, 20 and theoretical 12, 13, 21, 22, 23, 24 studies have provided evidence that peptide bond breaking is the result of a mechanism where a water molecule is activated by an aspartate residue and it then attacks as a nucleophile on a carbonyl carbon of the substrate peptide chain. Nevertheless, in the past 30 years different mechanisms for the reaction catalyzed by aspartic proteases have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…In the QM/MM studies of HIV-1pr, the aspartic dyad and model substrates are usually included in the QM representation. 44,45 These studies were successful in clarifying some fundamental aspects of the substrate cleaving reaction. However, the bottleneck steps of the process are the substrate recognition and binding.…”
Section: Multiscale Modeling Of Proteins Tozzinimentioning
confidence: 99%